ALAT SCORING BOARD UNIVERSAL BERBASIS MIKROKONTROLER ATMega 16 - , BIMA RICHARDO SIHOMBING, Nur Sulistyawati,ST.,MT. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Planning and making universal scoring board for various types of sporting events in semi automatic based Mikrokontroller ATMega 16. Making the scoring board is one such utilization of ic atmega 16 at sports. By using the scoring board is expected to facilitate human work for counting the score and time matches on many kinds of sports, so as to diminish extra power. Scoring board in the series use ATMega 16 IC and IC 74LS192 Decade Counter as the main components that are used to manipulate data so that it can display the time and score of each team competed in the Seven Segment display. Circuit is also equipped with LCD(Liquid Crystal Display) used to set a menu of choices sports event.